A Teacher-Made Test for an Opinion Paragraph: Insights from Design-Based Research (DBR) - Mukminatus Zuhriyah; Nur Mukminatien; Soo Kum Yoke; Suhono Suhono (CV. Creative Tugu Pena, 2025)
In English as a Foreign Language (EFL) teaching and learning, teachers frequently design their own tests to measure students’ skills, monitor progress, and evaluate instructional effectiveness. However, most previous research on teacher-made tests in EFL writing has centered on essay types such as descriptive, argumentative, narrative, expository, and comparison-contrast, leaving opinion paragraphs relatively underexplored. Addressing this gap, the present study describes the systematic development and validation of a teacher-made test specifically designed to assess opinion paragraphs. Conducted in a paragraph writing course at a private university in East Java, the study adopts a genre-based approach and draws on the design-based research (DBR) framework proposed by Cavallaro and Sembiante (2021). The instrument consists of two components: a writing prompt and an analytic scoring rubric. Its quality was ensured through a comprehensive validation process, including content and face validity (involving two writing instructors and eight students) and inter-rater reliability testing by two trained raters. The resulting test provides a cohesive, valid, and reliable formative assessment tool for evaluating EFL learners’ opinion paragraph writing. The inter-rater reliability coefficient (r = 0.85) indicates a strong positive correlation, supporting the consistency and reliability of the scoring rubric. This study not only contributes to the enhancement of teachers’ assessment literacy but also offers a practical model for developing and validating classroom-based writing assessments in EFL contexts.